Kerajaan Majapahit Dinamika Dalam Sejarah Nusantara - Nadalina, Masayu Laila; Susanti, Retno; Hudaidah, Hudaidah (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
The history of the 13th-century Majapahit Kingdom, which was still impacted by the Hindu-Buddhist period, is both illustrious and terrible. Majapahit has a wide range of data sources, including literature, artifacts, and international news. This made it possible to learn a lot about its past. Historical events can serve as a foundation for understanding history.Investigating the political, economic, social, and cultural phenomena that took place in the Majapahit kingdom and the effects they had on Southeast Asia's history and civilization is the goal of this study. Using a historical method, this study examines primary and secondary sources, including inscriptions, old manuscripts, and other literary works and historical documents.Majapahit peaked under the rule of Patih Gajah Mada and King Hayam Wuruk. This kingdom became a major hub for trade in Southeast Asia and brought the majority of the archipelago together. Majapahit is renowned for its extremely quick cultural development, particularly in the fields of literature, art, and architecture. However, Majapahit fell in the 16th century due to internal issues such conflicts over monarch succession and dangers from rival kingdoms.Nonetheless, Majapahit's cultural legacy and impact are still present in Indonesian history and identity today.